Design, synthesis, and anticonvulsant effects evaluation of nonimidazole histamine H3 receptor antagonists/inverse agonists containing triazole moiety - Mingxia Song; Rui Yan; Yanhui Zhang; Dongfu Guo; Naiming Zhou; XianQing Deng (Taylor & Francis Group, 2020)
Histamine H3 receptors (H3R) antagonists/inverse agonists are becoming a promising therapeutic approach for epilepsy. In this article, novel nonimidazole H3R antagonists/inverse agonists have been designed and synthesised via hybriding the H3R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole moiety as anticonvulsant drugs. The majority of antagonists/inverse agonists prepared here exerted moderate to robust activities in cAMP-response element (CRE) luciferase screening assay. 1-(3-(4-(3-Phenyl-4H-1,2,4-triazol-4-yl)phenoxy)propyl)piperidine (3l) and 1-(3-(4-(3-(4-chlorophenyl)-4H-1,2,4-triazol-4-yl)phenoxy)propyl)piperidine (3m) displayed the highest H3R antagonistic activities, with IC50 values of 7.81 and 5.92 nM, respectively. Meanwhile, the compounds with higher H3R antagonistic activities exhibited protection for mice in maximal electroshock seizure (MES)-induced convulsant model. Moreover, the protection of 3m against the MES induced seizures was fully abrogated when mice were co-treated with RAMH, a CNS-penetrant H3R agonist, which suggested that the potential therapeutic effect of 3m was through H3R. These results indicate that the attempt to find new anticonvulsant among H3R antagonists/inverse agonists is practicable.